Vitamin D protects spermatogonia and Sertoli cells from heat stress damage by inhibiting NLRP3 - Chu, Han; Deng, Qi-Fei; Fang, Yuan (Frontiers in Pediatrics, 2025)
IntroductionCryptorchidism can damage cells in the cryptorchid testes due to elevated local temperatures, potentially impacting the fertility of the child in adulthood. Research indicates that vitamin D enhances sperm quality in adult males. This study aimed to explore whether vitamin D inhibits NLRP3 activation, thus helping to mitigate heat stress damage to testicular spermatogenic and Sertoli cells.Materials and methodsFive cases of normal testicular tissue adjacent to a tumor (testis removed due to tumorous growth) and five cases of atrophied cryptorchid testicular tissue (testis removed) were analyzed for immunohistochemistry to determine NLRP3 expression in cryptorchid tissue. In Phase I, spermatogonia (GC-1) and Sertoli cells (TM4) were separated into blank and heat stress groups. Apoptosis, inflammatory factor levels, and the expression of Bcl-2 and NLRP3 genes and proteins were measured at 2, 6, and 10 h after heat stress treatment. In Phase II, the cells were re-cultured and divided into three groups: heat stress, siRNA + heat stress, and VD + heat stress. After 10 h, the apoptosis, inflammatory factor levels, and gene and protein expressions of Bcl-2 and NLRP3 were reassessed in each group.ResultsImmunohistochemistry indicated NLRP3 expression in cryptorchid tissue. Phase I, extending heat stress duration led to increased apoptosis in spermatogonia (GC-1) and testicular Sertoli cells (TM4), heightened levels of inflammatory factors, reduced BCL-2 expression, and elevated NLRP3 expression compared to the control group. Phase II, both the siRNA + heat stress and VD + heat stress groups showed decreased apoptosis in spermatogonia and Sertoli cells, lower inflammatory factor levels, increased BCL-2 expression, and decreased NLRP3 expression compared to the heat stress-only group, with statistically significant differences (P < 0.05).ConclusionsThis is the first time we found the expression of NLRP3 in cryptorchidism. Vitamin D can inhibit the expression of NLRP3 and reduce the damage of heat stress on testicular spermatogenic cells and Sertoli cells, and play a protective role for testicular spermatogenic cells and Sertoli cells. This provides a theoretical basis for preserving testicular function during the “treatment gap” in boys with cryptorchidism who have not received surgical treatment.